Medulloblastoma: recurrence and metastasis - Aref, Donya (CNS Oncol, 2013)
Medulloblastoma is the most common malignant brain tumor of childhood. Although there is now long-term survival or cure for the majority of children, the survivors bear a significant burden of complications due, at least in part, to the intense therapies given to ensure eradication of the tumor. Significant efforts have been made over the years to be able to distinguish between patients who do and do not need intensive therapies. This review summarizes the history and current state of clinical risk stratification, pathologic diagnosis and genetics. Recent developments in correlation between genetics and pathology, genome-wide association studies and the biology of medulloblastoma metastasis are discussed in detail. The current state of clinical treatment trials are reviewed and placed into the perspective of potential novel therapies in the near term.